An Exact Model for Rotor Field-Oriented Control of Single-Phase Induction Motors - Mohammad Jannati; Ali Monadi; Sajad A. Anbaran; Nik Rumzi Nik Idris; Mohd Junaidi Abdul Aziz (Institute of Advanced Engineering and Science, 2014)
This work presents a new Rotor Field-Oriented Control (RFOC) technique for single-phase Induction Motors (IMs). The proposed method uses two rotational transformations, which extract from the steady-state equivalent circuit of single-phase IM. It is proved by using proposed rotational transformations, the single-phase IM asymmetrical equations change into symmetrical equations. In the proposed technique, the assumption of (Mq/Md)2=Lqs/Lds=a2 which is usually used in other FOC of single-phase IMs, is not considered. Performance of the proposed technique is assessed using MATLAB/SIMULINK. Extensive simulation results show the performance and correctness of the proposed method.